Rancang Bangun Automatic Liquid Filling Machine Berbasis Internet of Things Menggunakan NodeMCU dan Telegram - Seno Prasetyo; Indra Yustiana; Anggun Fergina (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2023)
Technology and industry are inseparable. Technology has made human work easier and more efficient and minimized the occurrence of errors. Recently, small household industries (home industry), specifically liquid product industries such as milk, syrup, fruit juice, and others, still use manual filling. This process requires a relatively long charging time. Automatic mechanical systems for filling liquids into bottles are a kind of technological advancement in the industrial world. The system helps the process of filling liquids into bottles precisely and quickly. It is necessary to design small-scale Internet of Things-based tools for the home industry by utilizing NodeMCU as a control system, and InfraRed and Ultrasonic as sensors. Arduino IDE as programming sketch software and Telegram as a data monitoring application. Based on this background, this study aims to create an automatic system for filling liquids into bottles based on the Internet of Things by monitoring data via telegrams. The results of the tool testing show that the installed infrared sensor can detect the filling of liquid in bottles consistently with a period of 5 seconds for each bottle. The Telegram application that is integrated with the tool can provide notifications of the amount of liquid in the main container automatically at the end of the filling process. Likewise when the amount of liquid is in critical condition. Overall, each component of this tool has worked well.